The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fneur.2021.732939
|View full text |Cite
|
Sign up to set email alerts
|

Health Conditions in Adults With Cerebral Palsy: The Association With CP Subtype and Severity of Impairments

Abstract: Aim: To determine the prevalence of common health conditions in adults with cerebral palsy (CP) and to identify associations with the CP subtype or the severity of impairments.Methods: A population-based, cross-sectional study of 153 adults with CP born from 1959 to 1978 (87 males, 66 females; median age 48 years 3 months, range 37–58 years; 41% with unilateral spastic, 36% bilateral spastic, 19% dyskinetic, and 4% with ataxic CP). Data was gathered through interviews, physical assessments, and medical record … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(57 citation statements)
references
References 35 publications
1
56
0
Order By: Relevance
“…This ratio was less skewed when considering anxiety as it occurred with a 3–2 ratio in patients with ID. This is similar to McMorris et al ( 11 ), Jonsson et al ( 16 ), and Whitney et al ( 9 ) who showed a prevalence of psychotic disorders in patients with CP and ID and a prevalence of anxiety disorders in patients with only CP.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This ratio was less skewed when considering anxiety as it occurred with a 3–2 ratio in patients with ID. This is similar to McMorris et al ( 11 ), Jonsson et al ( 16 ), and Whitney et al ( 9 ) who showed a prevalence of psychotic disorders in patients with CP and ID and a prevalence of anxiety disorders in patients with only CP.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, Van Gorp et al ( 15 ) showed that patients with GMFCS I had fewer depressive symptoms when compared to the age-matched reference population. By contrast, Jonsson et al ( 16 ) when compared different levels of GMFCS and CFCS found no significant differences in psychiatric symptoms, depression, and anxiety. Our results, therefore, are in agreement with those that showed an increased risk of psychiatric disorders when a severe motor impairment is present.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Prevalence of diabetes (type not specified) was 9.6% (95% CI = 6.9%-12.6%; I 2 = 99.3%, p < 0.01; n = 11 723 out of 71 815; 15 studies). 28,[31][32][33][34][37][38][39][40][41][42][43][44][45][46] Age-adjusted prevalence of diabetes reported in one study was 9.2%. 47 The prevalence of diabetes among non-ambulatory individuals with CP in two studies was 7.0% and 8.6%.…”
Section: Endocrine Diseasesmentioning
confidence: 92%
“…The prevalence of pressure ulcers reported by two studies was 7.8% and 9.2%. 36,37 The prevalence of pressure ulcers was 1.8% among ambulatory individuals and 27.9% among non-ambulatory individuals with CP. 33 The prevalence of pressure ulcers was 35.3% among people with intellectual disability and 1.7% among people without intellectual disability.…”
Section: Diseases Of the Skinmentioning
confidence: 99%